Study on TiO2 Extraction from Ilmenite Sand in Ketapang Regency Through Various NaOH Molar Ratios - Sy. Indra Septiansyah; Herman; Rahmat Nur Hidayatulloh; Alesya Rahmadita (BRIN Publishing, 2026)
Titanium Dioxide (TiO2) is a high-value inorganic material widely used in various industrial sectors, including paints and coatings, cosmetics, and ceramics, as well as in photocatalytic energy and environmental applications. One of the main sources of TiO2 is the mineral ilmenite (FeTiO3), which is abundant in iron sand deposits in Ketapang Regency, West Kalimantan. However, its use has thus far been limited to raw mining activities without downstream processing, resulting in relatively low economic value added. This study aims to extract TiO2 from Ketapang ilmenite sand through the alkali fusion method using NaOH with molar ratios of 1:1, 1:2, 1:3, and 1:4. The fusion product (frit) was subsequently washed with distilled water, leached with 37% HCl solution, and precipitated using NH4OH to obtain Ti precipitates, which were then characterized using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Scanning Electron Microscopy coupled with Energy Dispersive X-ray (SEM-EDX). Initial characterization revealed that ilmenite sand contained 43.78% TiO2, 27.84% Fe2O3, and 15.34% ZrO2 along with minor amounts of other associated minerals. XRD analysis of the extracted product confirmed the presence of diffraction peaks matching the standard TiO2 pattern, with relative intensity reaching 100% at molar ratios of 1:1 to 1:4. The dominant crystalline phase identified was anatase. Morphological observations by SEM revealed TiO2 particles with nano–submicron crystal structures and rough surfaces characteristic of anatase, while EDX analysis confirmed titanium as the dominant surface element, with an atomic composition up to 90.21%.